Taking on the Habit: Kierkegaardian Faith as an Aristotelian Virtue - Rojas, Fernanda (Religions, 2023)
In this article, we would like to argue that the notion of faith, as seen in the anthropology that Kierkegaard presents in works such as The Sickness unto Death or Postscript, among others, shows striking similarities with the Aristotelian ethics of virtue. In a more specific manner, we wish to propose that faith can be interpreted as a virtue in the Aristotelian sense since one can find the following three aspects in it: (1) faith is a state based on habit; (2) faith makes human beings good; and (3) faith makes the human being perform her characteristic activity well. In our view, these features correspond to Aristotle’s definition of virtue: “If this is so in all cases, the virtue of a human being too will be the state that makes a human being good and makes him perform his characteristic activity well”. (Nicomachean Ethics, 1106a).